Apple TIME FOR COFFEE contributes to freezing tolerance by promoting unsaturation of fatty acids. (January 2021) - Zhao, Caide; Liu, Xiaofang; He, Jieqiang; Xie, Yinpeng; Xu, Yao; Ma, Fengwang; Guan, Qingmei
Highlights: MdTIC is a target of R2R3 transcription factor MdMYB88 and MdMYB124. Disruption of MdTIC reduced apple freezing tolerance. MdTIC regulates plant cold tolerance by mediating the expression of cold-responsive genes and fatty acid composition. Abstract: Freezing stress is a major environmental factor that threatens the growth and development of fruit trees. MdMYB88 and its paralogue MdMYB124 have been identified as pivotal regulators in apple ( Malus × domestica ) freezing stress tolerance. Here, we demonstrated that a target of MdMYB88 and MdMYB124, TIME FOR COFFEE ( TIC ), contributes to freezing tolerance in apple. MdMYB88 and MdMYB124 directly bound the MdTIC promoter and positively regulated its expression under cold conditions. MdTIC RNAi plants displayed reduced freezing tolerance when MdTIC expression was repressed. Moreover, MdTIC RNAi plants lowered antioxidant enzyme activity. Transcriptome profiling revealed altered expression of cold-responsive genes in MdTIC RNAi plants under cold conditions, including MdPLC2, MdMKK2, and MdICE1 . We also discovered that disordered MdTIC expression changed the saturation of fatty acids. Taken together, our data suggest that MdTIC is required for apple to tolerate freezing by mediating the expression of cold-responsive genes and fatty acid composition.